(untitled) (San Diego, CA., 2000)
This volume addresses oxidant-reduction or redox and antioxidant sensitive molecular mechanisms and how they are implicated in different disease processes. Possible strategies to pharmacologically and/or nutritionally manipulate such redox-sensitive molecular responses are emphasized.
Keywords: Genes